Regulation of Biological Nitrogen Fixation - Halbleib, Cale M.; Ludden, Paul W. (The Journal of nutrition, 2000)
Biological nitrogen fixation, a process found only in some prokaryotes, is catalyzed by the nitrogenase enzyme complex. Bacteria containing nitrogenase occupy an indispensable ecological niche, supplying fixed nitrogen to the global nitrogen cycle. Due to this inceptive role in the nitrogen cycle, diazotrophs are present in virtually all ecosystems, with representatives in environments as varied as aerobic soils (e.g., Azotobacter species), the ocean surface layer (Trichodesmium) and specialized nodules in legume roots (Rhizobium). In any ecosystem, diazotrophs must respond to varied environmental conditions to regulate the tremendously taxing nitrogen fixation process. All characterized diazotrophs regulate nitrogenase at the transcriptional level. A smaller set also possesses a fast-acting post-translational regulation system. Although there is little apparent variation in the sequences and structures of nitrogenases, there appear to be almost as many nitrogenase-regulating schemes as there are nitrogen-fixing species. Herein are described the paradigms of nitrogenase function, transcriptional control and post-translational regulation, as well as the variations on these schemes, described in various nitrogen-fixing bacteria. Regulation is described on a molecular basis, focusing on the functional and structural characteristics of the proteins responsible for control of nitrogen fixation.